Pemberdayaan Remaja melalui Workshop Interaktif untuk Penguatan Nilai-Nilai Karakter Positif di Kota Malang dan Makassar - Edy, Dewi Fatmasari; Nurmalitasari, Femmi; Muhiddin, Syurawasti; Ainiyah, Hilda Rosa; Putri, Nazwa Nayla Divani; Febrianti, Widi (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
This community service activity aims to empower adolescents through interactive workshops based on experiential learning to strengthen positive character values ​​amidst the complex psychosocial challenges of the digital era. The background of this program is motivated by the rise of risks such as cyberbullying, social isolation, and identity crises, which require adaptive character-building strategies so that adolescents can adapt healthily and productively. This workshop involved 33 participants aged 13-19 years located in Malang City and Makassar City, to reach diverse socio-cultural contexts. The implementation method was designed in a participatory and contextual manner, including focus group discussions, role-play simulations, educational games, and in-depth personal reflection. Impact evaluation was conducted using pre-test and post-test instruments, complemented by analysis of participant reflection sheets. The results of the quantitative analysis showed a significant increase in average scores between the pre-test and post-test. This increase indicates an expansion of cognitive understanding of the concept of character values, recognition of self-strengths, as well as improved assertive communication skills and emotional management. Meanwhile, qualitative analysis of participant reflections revealed increased self-awareness, intrinsic motivation to apply positive values ​​in daily life, and the emergence of community action ideas that benefit the surrounding environment. This program has proven effective in encouraging holistic positive change, encompassing the cognitive, affective, and behavioral aspects of adolescents. Therefore, this workshop model is relevant and highly recommended for continued development and implementation in various character-building programs for the younger generation. Keywords: Youth empowerment, Positive character, Experiential learning, Interactive workshop, Self-development. Kegiatan pengabdian masyarakat ini bertujuan untuk memberdayakan remaja melalui workshop interaktif berbasis experiential learning guna memperkuat nilai-nilai karakter positif di tengah kompleksitas tantangan psikososial era digital. Program ini dilatarbelakangi oleh maruhnya risiko seperti perundungan dunia maya, isolasi sosial, dan krisis identitas, yang menuntut strategi penguatan karakter yang adaptif agar remaja mampu beradaptasi secara sehat dan produktif. Workshop ini melibatkan 33 peserta berusia 13-19 tahun yang berlokasi di Kota Malang dan Kota Makassar, guna menjangkau konteks sosio-kultural yang beragam. Metode pelaksanaan dirancang secara partisipatif dan kontekstual, mencakup diskusi kelompok terfokus, simulasi peran (role-play), permainan edukatif, dan refleksi pribadi yang mendalam. Evaluasi dampak dilakukan menggunakan instrumen pre-test dan post-test, dilengkapi dengan analisis lembar refleksi peserta. Hasil analisis kuantitatif menunjukkan peningkatan skor rata-rata yang signifikan antara pre-test dan post-test. Peningkatan ini mengindikasikan adanya perluasan pemahaman kognitif terhadap konsep nilai karakter, pengenalan kekuatan diri, serta peningkatan keterampilan komunikasi asertif dan pengelolaan emosi. Sementara itu, analisis kualitatif dari refleksi peserta mengungkapkan peningkatan kesadaran diri (self-awareness), motivasi intrinsik untuk menerapkan nilai-nilai positif dalam kehidupan sehari-hari, serta munculnya ide-aksi komunitas yang bermanfaat bagi lingkungan sekitarnya. Program ini terbukti efektif dalam mendorong perubahan positif yang holistik, mencakup aspek kognitif, afektif, dan perilaku remaja. Oleh karena itu, model workshop ini relevan dan sangat dianjurkan untuk dikembangkan serta diimplementasikan secara berkelanjutan dalam berbagai program penguatan karakter generasi muda. Kata Kunci: Pemberdayaan remaja, Karakter positif, Experiential learning, Workshop interaktif, Pengembangan diri.